2009
DOI: 10.1177/0883073808321048
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Ultrasound Lesions in the NICU Predict Cerebral Palsy at Age 2 Years in Children Born at Extremely Low Gestational Age

Abstract: Our prospective cohort study of extremely low gestational age newborns evaluated the association of neonatal head ultrasound abnormalities with cerebral palsy at age 2 years. Cranial ultrasounds in 1053 infants were read with respect to intraventricular hemorrhage, ventriculomegaly, and echolucency, by multiple sonologists. Standardized neurological examinations classified cerebral palsy, and functional impairment was assessed. Forty-four percent with ventriculomegaly and 52% with echolucency developed cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 57 publications
3
91
0
6
Order By: Relevance
“…[17][18][19]36,38,40 However, while WMD may be sufficient for adverse neurobehavioral outcomes, it may not be necessary as CP and other adverse neurobehavioral outcomes are known to occur in the absence of WMD. [41][42][43][44][45] Our study is the first, to date, demonstrating an Figure 5. Number of processes of cultured neuronal cells at DIV 3.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19]36,38,40 However, while WMD may be sufficient for adverse neurobehavioral outcomes, it may not be necessary as CP and other adverse neurobehavioral outcomes are known to occur in the absence of WMD. [41][42][43][44][45] Our study is the first, to date, demonstrating an Figure 5. Number of processes of cultured neuronal cells at DIV 3.…”
Section: Discussionmentioning
confidence: 99%
“…21 Other investigators have also shown that infants with isolated IVH and without associated echolucency and/ or ventriculomegaly are only slightly more likely to have cerebral palsy than those with normal ultrasound studies. 22 Limitations of the study include difficulty in ascertainment of time of onset of some complications. For example, most IVH occurs in the first 3 to 5 days, 23,24 but some infants may have their first cranial sonogram after 7 days, thereby delaying the diagnosis but not actual timing of the morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Cognitive impairment is the most frequent developmental problem identified in extremely premature survivors. [3][4][5] Impaired early cognitive function, assessed with the Bayley Scales of Infant Development (BSID), is moderately predictive of cognitive function at school age. 6 Antenatal factors associated with cognitive limitations in ELGANs include unmarried mother, 7 minority race, 5 fewer years of education, 5 lack of antenatal steroid exposure, 5,8 maternal smoking during pregnancy, 8 and preeclampsia.…”
mentioning
confidence: 99%